(untitled) (Антропологический форум / Forum for Anthropology and Culture, 2020)
This discussion is dedicated to the question of whether it is possible to overcome the power asymmetry between researchers and their subjects in the study of childhood, or at the very least to reduce the gulf between researchers and the objects of their studies. The ‘new sociology of childhood’ places the individual personality of the child and his / her personal interests at the centre of scholarly investigation, though its central presuppositions remain in some respects controversial. The focus on children’s subjectivity in academic work is related to the public acknowledgement of children’s agency as political and legal subjects. In this framework, the participants discuss the ethical and methodological problems related to work with children as subjects in childhood studies.